Philippe Djian, un artisan du verbe aux marges de la littérature - Bouchoucha, Myriam (Journal of Human Sciences, 2016)
This article tries to present a controversial author : Philippe Djian.Famous but paradoxically unknown, he occupies a special position in contemporary french literature.Literary institution has long considered his works as popular lietrature. His work is classified by criticism as resolutely modern. Relying on American inspiration, it reveals a demanding way of writing, an original universe that suits his time. Djian’s works deserve to raise debate and ask interesting questions : where are the frontiers between literature and popular literature  situated? Does literary inspiration have limits ? When a writer becomes an author ?